2004
DOI: 10.1038/nmat1203
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling of atomic vacancies at an oxide/intermetallic alloy interface

Abstract: Oxide layers grown on the surface provide an effective way of protecting metallic materials against corrosion for sustainable use in a broad range of applications. However, the growth of cavities at the metal/oxide interface weakens the adherence of the protective layer and can promote its spallation under service conditions, as observed for alumina layers formed by selective oxidation of aluminide intermetallic alloys used in high-temperature applications. Here we show that direct atomic-scale observations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 20 publications
12
67
0
Order By: Relevance
“…Neutral chemistry.-In NC1 solutions, the concentrations of chloride ions and sulfate ions were 0.65 mol/L and 0.15 mol/L respectively; the effect of chloride ions on the passive film is the dominant one though it is known that a small amount of sulfates may mitigate the detrimental effect of chlorides. The adsorption of chloride ions into a passive film may increase the cation vacancy concentration in two possible ways: (1) Chlorides may enhance the transfer of metal ions from the oxide to the electrolyte; 62 (2) Chlorides may fill anion vacancies according to the point defect model (PDM). 29,30,33 As a consequence of mechanism (1), the concentration of surface cation vacancies increases in solutions containing chloride.…”
Section: Effects Of Ph On Mechanisms Of Sulfur-induced Passivity Degrmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral chemistry.-In NC1 solutions, the concentrations of chloride ions and sulfate ions were 0.65 mol/L and 0.15 mol/L respectively; the effect of chloride ions on the passive film is the dominant one though it is known that a small amount of sulfates may mitigate the detrimental effect of chlorides. The adsorption of chloride ions into a passive film may increase the cation vacancy concentration in two possible ways: (1) Chlorides may enhance the transfer of metal ions from the oxide to the electrolyte; 62 (2) Chlorides may fill anion vacancies according to the point defect model (PDM). 29,30,33 As a consequence of mechanism (1), the concentration of surface cation vacancies increases in solutions containing chloride.…”
Section: Effects Of Ph On Mechanisms Of Sulfur-induced Passivity Degrmentioning
confidence: 99%
“…If these vacancies penetrate into the metal phase at a rate slower than their transport through the oxide, they accumulate at the metal-oxide interface. Marcus et al 62 found evidence for the formation and self-assembly of clusters of oxygen vacancies at a metal-oxide interface. When an oxide grows on the surface of a metal, after the first monolayer is formed, transport processes within the oxide become a factor.…”
Section: Effects Of Ph On Mechanisms Of Sulfur-induced Passivity Degrmentioning
confidence: 99%
“…52 Compared to natural oxidation, the rate of oxygen intake into the oxide film in photon-assisted growth is significantly increased due to an activation-barrier reduction. The enhanced oxidation kinetics due to elimination of the chemisorption barrier as well as lowered activation-energy barrier for ionic migration is responsible for the increased uptake of oxygen in the near-surface region of the passive-oxide film.…”
Section: G Corrosion Resistance Of Ultrathin Oxidesmentioning
confidence: 99%
“…A viable approach for the synthesis of ultrathin oxide films is based on the selective oxidation of suitable bimetallic alloys [18][19][20][21][22]. The prototypical example is an ultrathin alumina film on the NiAl(110) substrate [18,23], which has been widely used as a support in model catalytic studies [1,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%